Development of Integrated Curriculum Student Worksheet to Train Student Scientific Literacy Skills in Reaction Rate Materials - Varradiah Choirun Nisa'; Bertha Yonata (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
Development of Integrated Curriculum Student Worksheet to Train Student Scientific Literacy Skills in Reaction Rate Material. This research aims to describe the feasibility of integrated curriculum student worksheet to train student scientific literacy skills in reaction rate material assessed from validity, practical, and effectiveness criteria. This research uses Research and Development (RD) method until limited the trial stage. The instruments are the review and validation sheet, activities observation sheet, student questionnaire sheet, and science literacy skill test sheet. The developed student worksheet was tested on 13 students of XI grade at State Senior High School (SMAN) of 1 Grati Pasuruan that already accept reaction rate material. The validity of student worksheet is obtained based on assessment from two chemistry lecturers of Universitas Negeri Surabaya and two chemistry teachers of State Senior High School (SMAN) of 1 Grati. The validation consists of content and construct validity by expert obtained a percentage sequentially are 91,46% and 88,96% with both in very valid category. The practical of student worksheet is obtained based on student response and activities observation who get positive response of 98,82%  and relevant student activities result of 98,83% both with very valid practical category. The effectiveness of student worksheet is obtained based on test result of student science literacy skills where student declared as complete with value range 83,9-96,8 and N-gain value of 0,8 with high criteria. Each domain of scientific literacy skills include science context, science knowledge, science competencies, and attitude towards science got percentages sequestially 90%, 91%, 91%, dan 96%.